First results of ionospheric plasma blob observations in the African topside ionosphere during a deep solar minimum using Swarm satellites - Adebayo, Oluwasegun M.; Rabiu, Babatunde; Pimenta, Alexandre A.; Chian, Abraham C.-L.; Dare-Idowu, Oluwakemi; Okoh, Daniel I.; Akerele, Aderonke (Frontiers in Astronomy and Space Sciences, 2025)
This study presents the first comprehensive investigation of low-latitude ionospheric plasma blobs in the African sector during the deep solar minimum period from January 2018 to December 2020, using data from the Swarm satellite mission. Plasma blobs are localized regions of enhanced electron density, often associated with equatorial plasma bubbles (EPBs). While EPBs are traditionally considered a key mechanism for blob formation, our analysis reveals that 55.2% of plasma blob events occurred independently of EPBs, indicating the influence of additional processes such as the fountain effect, local thermospheric winds, and lower atmospheric forcing. The results show that plasma blobs predominantly occur between 16:00 UT and 02:00 UT, with a notable concentration in northern Africa, suggesting regional susceptibility to ionospheric irregularities. Electron density enhancements within blobs range from 5% to over 100%, and with a median of approximately 25%. Cases with enhancements exceeding 100% are likely linked to geomagnetic storm-time activity. This study also identifies hemispheric asymmetry in blob occurrence, potentially driven by seasonal shifts in the Intertropical Convergence Zone (ITCZ), gravity wave activity, and magnetic field geometry unique to the African region. These findings highlight the complex, multifactorial nature of plasma blob formation in the African ionosphere and provide a critical baseline for future studies in this underexplored region. Understanding these dynamics is essential for improving models of ionospheric irregularities and mitigating their impacts on satellite communication and navigation systems over Africa.